A Real-Time Space Availability Detection in Smart Parking Systems Using Infrared Sensor and Microcontroller Atmega 328p - Putri, Fidel Lusiana (ULTIMA Computing, 2025)
In the growing digital era, vehicles have become a staple for daily mobility. This poses a significant parking problem, especially in urban areas with limited parking spaces. The search for parking spaces often leads to congestion, air pollution, fuel waste, and frustration for drivers. This research aims to develop an Internet of Things (IoT) based smart parking system using infrared sensors and an ATmega328p microcontroller to detect the availability of parking slots in real time. This system provides information to the driver through an LCD screen installed at the entrance of the parking area. The methods used in this research are direct testing and tool prototyping. The results show that this smart parking system can detect the availability of parking slots with high accuracy and provide real-time information to drivers, thereby reducing congestion and improving parking management efficiency.